White Matter Injury in Stroke and CNS Disease - Baltan, Selva; Carmichael, S. Thomas; Matute, Carlos; Xi, Guohua; Zhang, John H.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
The first book to provide a systematic expert summary of normal white matter morphology as well as white matter injury following stroke and other CNS injuries. White matter injury can result from both ischemic and hemorrhagic stroke as well as a host of other CNS diseases and conditions such as neonatal injuries, neurodegenerative disorders including Alzheimer's disease, traumatic brain injuries, carbon monoxide poisoning, and drug or alcohol overdoses. The extent of white matter injury is extremely important to patient outcomes. Several recent technological developments including advanced neuroimaging and the breeding of new rodent models of white matter injury have provided growing insight into initial damage and repair after a stroke or other damaging event.
White matter: Basic principles of axonal organization and function -- Electrophysiology evaluation of white matter injury -- CADASIL and animal models -- Neuroimaging of White Matter Injury: A Multimodal Approach to Vascular Disease -- Diffusion MRI Biomarkers of White Matter Damage in Traumatic Brain Injury -- Mechanisms underlying the selective vulnerability of developing white matter -- Neonatal experimental white matter injury -- Focal ischemic white matter injury in experimental models -- Global ischemic white matter injury in patients -- Experimental global ischemia and white matter injury -- White Matter Injury after Experimental Intracerebral Hemorrhage -- White Matter Repair after Ischemic Injury -- White Matter Injury in Subarachnoid Hemorrhage in Humans -- Neurodegenerative diseases and white matter injury in patients -- Unmyelinated and myelinated axons exhibit differential injury and treatment response following traumatic brain injury -- Age-Dependent Mechanisms Of White Matter Injury After Stroke -- White matter damage in multiple sclerosis -- Calcium dyshomeostasis in white matter injury -- Inflammation and white matter injury in animal models of ischemic stroke -- Oxidative stress in white matter injury -- Acute Axonal Injury in White Matter Stroke -- Mitochondria disorder and white matter injury -- Heave metal and white matter injury -- Anesthesia and white matter injury.
Keywords: Medicine; Neurosciences; Neurology; Neurobiology; Biomedicine; Neurosciences; Neurology; Neurobiology